HUBUNGAN ANTARA PENGAWASAN DAN KOMPENSASI DENGAN PRESTASI KERJA GURU DI SMA NEGERI SE-KOTA BEKASI - Mukaromah Mukaromah (Jurnal Manajemen Pendidikan, 2011)
This research aims to determine the relationship between (1) control with teacher’s performance at public SMA in Bekasi,Districk (2) compensation with teacher’s performance at public SMA in Bekasi,Districk, (3) control and compensation together with teacher’s performance at public SMA in Bekasi Districk.The research method using survey by correlational approach. This research used sample of 90 employees (teachers and principals), and 20 employees (teachers and principals) for trial, and selected based on a simple random technique (Simple Random Sampling). Study toward in public Senior High School in Bekasi Districk. Technique data collecting was using the instrument in the form of questionnaire. This instrument is calibrated with the test item validity and reliability coefficients. To test the validity of using Pearson Product Moment correlation, while the reliability coefficient is calculated using the formula of Cronbach Alpha. The results showed that: First, there is a positive relationship between control with performance. Secondly, there is a positive relationship between compensation with the performance. Third, there is a positive relationship between control and compensation together with performance. The implications of this research is teacher’s performance in Bekasi can be enhanced through control of the Principal and an increase in compensation.